A case of immune reconstitution syndrome complicating progressive multifocal leukoencephalopathy after kidney transplant: Clinical, pathological, and radiographic features. Issue 5 (3rd September 2019) - Jackowiak, Eric; Shah, Nirav; Chen, Huiwen; Ojha, Ajitesh; Doyle, John; Shepler, Anne; Bogdanovich, Tatiana; Silveira, Fernanda P.; Haidar, Ghady
Abstract: Progressive multifocal leukoencephalopathy (PML) is a life‐threatening central nervous system (CNS) disorder, most commonly described in patients infected with the human immunodeficiency virus (HIV). Limited data exist on its natural history and treatment in solid organ transplant (SOT) recipients. A complication of PML is the immune reconstitution inflammatory syndrome (IRIS), which develops after T cell reconstitution and can have severe consequences when it occurs in the CNS. While well described in HIV‐infected individuals, its clinical features, diagnosis, and treatment after SOT are largely unknown. We report a case of a kidney transplant recipient who was diagnosed with PML and developed significant worsening of her symptoms upon reduction of immunosuppression. Thallium SPECT showed avid uptake suggestive of lymphoma, but the diagnosis of PML‐IRIS was ultimately established by brain biopsy. She survived with nearly complete restoration of her functional status after a prolonged steroid taper.